The Resolution of the Third International conference Scientific research in Antarctica in 2006 - S. M. Nikolayenko (Ukrainian Antarctic Journal, 2006)
On May 29 - June 2, 2006 the Ministry of Education and Science of Ukraine, National Academy of Sciences of Ukraine, National Antarctic Scientific Center (NASC) of the Ministry of Education and Science of Ukraine and NAtional Aviation University organized and held the Third International Ukrainian Antarctic Conference (III UAC 2006). The conference was attended by 124 researchers from five countries, e.g. Ukraine, Russia, Belorus, Spain and Germany. There were 134 presentations (103 oral and 31 poster) by 215 authors. All participants noted the wide range of scientific research presented, the high quality of the presentations, and the activity of their colleagues in the ensuing discussions. It was also noted the strengthening interdisciplinarity of the approaches to the methods and equipment used to study the natural phenomena and objects enabling a deeper and more robust understanding.